VARIAÇÃO MORFOLÓGICAS EM EICHHORNIA CRASSIPES (MART.) SOLMS EM TRÊS AMBIENTES AQUÁTICOS NO PANTANAL SUL - NASCIMENTO, A. M.; LUZ, G. P.; ANDRELLA, G. C.; OLIVEIRA, M. P.; FABIANO, V. S.; SANTOS, T. M. R. (ANAIS DO ENIC, 2016)
-